FAKTOR RESIKO TERJADINYA VARISES VENA TUNGKAI BAWAH (VVTB) PADA PRAMUNIAGA DI KOTA SEMARANG - Kuncoro Adi Pratiknyo; Asih Budiastuti; YL Aryoko Widodo (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Lower Limb Varicose Vein (LLVV) is (a condition where) normal vein (in leg) is dilated because of venous pressure increment. LLVV can create cosmetic problem because of discomfort feeling and unattractive appearance of patient’s leg. (LLVV can create discomfort and cosmetic problem because of unattractive appearance of patient’s leg)Objective: To investigate the factors associated with the occurrence of LLVV in salesclerk in Semarang.Method: This study is an analytical observational using case control study design. The samples were taken with consecutive sampling. Subjects were female salesclerk, comprised of 33 female salesclerk with LLVV (case) and 33 female salesclerk without LLVV (control). The collected data were the characteristics of subjects and related factor to LLVV. Data analysis was performed using SPSS Windows Ver. 20.Result: There was significant correlation in subjects with family history (p=0,009) and overweight/obesity (p=0,032) to the occurrence of LLVV. Subjects with family history had 4.2 times greater risk to suffer LLVV (OR=4.2; 95% CI=1.3 to 12.9) while subjects with overweight/obesity had 3.3 times greater risk to suffer LLVV (OR=3.3; 95% CI=1.0 to 10.1). There was no significant correlation in subjects with history of prolonged standing (p=0,105) to the occurrence of VVTB (OR=7,1; 95% CI=0.8 to 62.7).Conclusion: Risk Factors associated with the occurrence of LLVV are family history and overweight/obesity.